The influence of the use of Business networks and Social media on the interest in entrepreneurship in students of SMK Negeri 1 Amuntai - Vera Anggraini; Dwi Atmono; Monry Fraick Nicky Gillian Ratumbuysang; Muhammad Rahmatullah (Universitas Ibn Khaldun Bogor, 2023)
This study aims to to determine the influence of the use of business networks and social media on the interest in entrepreneurship at SMK Negeri 1 Amuntai. This study measures the effect of utilizing business networks and social media on entrepreneurial interests. One issue that has been addressed is the fact that social media is primarily used for hysteria while still having the ability to grow businesses. There is just a limited benefit of Jejaring business social media for conducting business.This type of research is Quantitative with Partial t test and Simultaneous F test. This research was conducted at SMK Negeri 1 Amuntai by taking questionnaire data. The results showed a partial t on the business network utilization variable (X1) to the entrepreneurial interest variable (Y) with a significant value (2-tailed) p = 0.000, < 0.05. which means that there is an influence of business network utilization on the entrepreneurial interests of students of SMK Negeri 1 Amuntai. Test results Partial t results on the social media utilization variable (X2) against the entrepreneurial interest variable (Y) get a significant value (2-tailed) p = 0.456, > 0.05 which means that there is no influence of social media use on the entrepreneurial interests of students of SMK Negeri 1 Amuntai. Then overall the results of the Simultaneous F test showed a significant number between business networks and social media on entrepreneurial interests with a significant value of p = 0.000, < 0.05 which means that there is a significant influence between business networks (X1) and social media (X2) on the interest in entrepreneurship (Y) in students of SMK Negeri 1 Amuntai. 05 which means that there is no influence of social media use on the entrepreneurial interests of students of SMK Negeri 1 Amuntai. Then overall the results of the Simultaneous F test showed a significant number between business networks and social media on entrepreneurial interests with a significant value of p = 0.000, < 0.05 which means that there is a significant influence between business networks (X1) and social media (X2) on the interest in entrepreneurship (Y) in students of SMK Negeri 1 Amuntai. 05 which means that there is no influence of social media use on the entrepreneurial interests of students of SMK Negeri 1 Amuntai. Then overall the results of the Simultaneous F test showed a significant number between business networks and social media on entrepreneurial interests with a significant value of p = 0.000, < 0.05 which means that there is a significant influence between business networks (X1) and social media (X2) on the interest in entrepreneurship (Y) in students of SMK Negeri 1 AmuntaiKeywords : Business Networks ; Social media; Entrepreneurial Interests